God's good man; a simple love-story - Corelli, Marie, 1855-1924; Dodd, Mead & Company (New York, Dodd, Mead & company, 1904)
A novel of romantic and religious aspect in which a young clergyman falls in love with an attractive wealthy woman moving in smart Edwardian society.
Mode of access: Internet.
Keywords: Bookbinding -- Specimens; Clergy -- England -- Fiction; Romance fiction, English; England -- Social life and customs -- Fiction; Love stories